Thomas & friends. Wild water rescue & other engine adventures [videorecording (DVD)]. - Awdry, W. (Thomas & friends, 2015)
Take the plunge with Thomas and his friends! Oily Diesel gets Percy all wet, while Gordon suffers the embarrassment of losing his buffer.